2016
DOI: 10.3329/fmcj.v11i1.30875
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentation and Risk Factors of Stroke-A Study of 100 Hospitalized Stroke Patients in Bangladesh

Abstract: Abstract:Stroke is one of the most common medical emergency. A total number of 100 randomly selected clinically and CT proven acute stroke patients were studied at medicine and neurology ward of Faridpur Medical College Hospital (FMCH), Faridpur from January to July, 2014 with a view to study the clinical features and risk factors of Stroke. Among 100 patients, stroke was found most commonly in 59-70 years age group. Ischaemic stroke was 56%, haemorrhagic stroke was 39% and haemorrhagic infarct was 5%. Most of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…A slightly higher male predominance was observed in this study with male to female ratio of 1.2:1. This finding was similar with the other study conducted by Saha et al, 20 with a male to female ratio of 1.6:1 and by Lange et al, 21 who found male to female ratio 1.5:1.The lower percentage of female stroke patients indicates either a low prevalence of stroke among females or a lower access of female stroke patients to the tertiary care hospital.…”
Section: Discussionsupporting
confidence: 91%
“…A slightly higher male predominance was observed in this study with male to female ratio of 1.2:1. This finding was similar with the other study conducted by Saha et al, 20 with a male to female ratio of 1.6:1 and by Lange et al, 21 who found male to female ratio 1.5:1.The lower percentage of female stroke patients indicates either a low prevalence of stroke among females or a lower access of female stroke patients to the tertiary care hospital.…”
Section: Discussionsupporting
confidence: 91%
“…Those studies showed that hypertension was more frequently present in case than control group which was similar to this study. According to Saha, et al (2016)17 hypertension was the commonest risk factor among the stroke patients which was found all of these studies. Diabetes mellitus was found 59.5% of case and 33.3% of control patient in this study.…”
mentioning
confidence: 94%